Replicating maximum periods of play in Australian football matches through position-specific drills - Wing, C.; Hart, N. H.; Ma'ayah, F.; Nosaka, K. (The Journal of Strength and Conditioning Research, 2023)
This study evaluated whether a position-specific drill replicates the running intensities of maximum ball in play (BiP) phases in competitive matches of Australian football (AF). Match data were collected on 32 AF players across 3 seasons (2019, 2020, 2021), with training session data collected from the same players across the 2021 season. Three position-specific training drills were created for defense, offense, and combination (defense and offense combined). Running intensities were compared between maximum BiP periods (e.g., periods with the highest metric per minute) from competitive matches and position-specific training drills, as well as between the 3 position-specific training drills using linear mixed models. The significance level was set at p < 0.05. Measures of distance (offense: 44.4 m·minute-1, defense: 83.5 m·minute-1, combination: 50.4 m·minute-1), high-speed running (offense: 76.7 m·minute-1, defense: 134.6 m·minute-1, combination: 89.6 m·minute-1), very high-speed running (offense: 26.7 m·minute-1, defense: 56.2 m·minute-1, combination: 55.0 m·minute-1), and high-intensity efforts (offense: 2.3 efforts·minute-1, defense: 3.0 efforts·minute-1, combination: 2.8 efforts·minute-1), relative to time were greater (p < 0.001) in all 3 position-specific training drills compared with BiP phases. All measured metrics were significantly (p < 0.001) greater in the defense drill compared with the offense drill, whereas distance, high-speed running, PlayerLoad, and accelerations were significantly (p < 0.001) greater when compared with the combination drill. These demonstrate that position-specific training drills that we created replicated or exceeded the running intensities recorded during matches based on maximum BiP periods. Position-specific training drills seem to be an attractive addition to AF players training regimens because it concurrently provides training for physical and technical actions (e.g., handballs).